2022
DOI: 10.1021/acs.iecr.1c04966
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of Liquid Flows in Cooling Tower Packing

Abstract: Wet cooling towers are used in many industrial processes. Although the heat transfer phenomena have been well studied in this kind of towers, the hydrodynamic behavior of air− water counter flows in industrial cooling tower packings remains unknown and has never been studied with local experimental approaches. Hydrodynamics are directly linked with operating issues such as packing fouling reducing cooling efficiency, or circuit operating optimization conditions that have an impact on the industrial plants' per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Jourdan et al [12] Material: PVC Specifications: It is composed of various thermoformed PVC sheets of 0.06 cm thickness and forms a sinusoidal pattern with a period of 5 cm and an amplitude of 1.7 cm.…”
Section: Shahali Et Al [48]mentioning
confidence: 99%
“…Jourdan et al [12] Material: PVC Specifications: It is composed of various thermoformed PVC sheets of 0.06 cm thickness and forms a sinusoidal pattern with a period of 5 cm and an amplitude of 1.7 cm.…”
Section: Shahali Et Al [48]mentioning
confidence: 99%
“…The experiments allowed the visualization and measurement of a falling water film along the packing sheets. Specific methods have been developed to measure main flow parameters such as the water film thickness and the packing wetting rate depending on the operating conditions [12]. In addition, CFD simulations were performed to obtain complementary data about liquid flow in cooling tower packing [13].…”
Section: Hydrodynamic Characterizationmentioning
confidence: 99%
“…Kariem [16] analyzed the counterflow WCT using high-density polyethylene fills and concluded that the cooling tower performed its best at the lowest L/G ratio. Jourdan [17] visualized the water film thickness of the falling water on the fills, and the wetting rate of the fills were studied. They observed the mean water film thickness in the range of 300-600 µm.…”
Section: Introductionmentioning
confidence: 99%